Strategic Analysis at the Electronic Components Company, Pinar del Río, Cuba - Rojas Hernández, Dairon (Ediciones UNL. Secretaría de Extensión de la UNL, 2021)
The following scientific research article aims to propose a paradigm shift in the management of the Electronic Components company, Pinar del Río. It determines the need to analyze the strategy of the entity as a prerequisite to achieve growth and development, and to transform and induce value. In addition, it describes how necessary it is for the organization to count on the strategic management’s contribution to the achievement of its goals as well as of the management group and employees’ objectives in order to be able to face uncertainty and risks about actions and reactions in markets.